Epidemiology of anaemia in children, adolescent girls, and women in Bhutan. (29th November 2018) - Campbell, Rebecca K.; Aguayo, Víctor M.; Kang, Yunhee; Dzed, Laigden; Joshi, Vandana; Waid, Jillian L.; Gupta, Suvadra Datta; Haselow, Nancy; West,, Keith P.
Abstract: Anaemia inhibits health and development in Bhutan. We estimated anaemia prevalence and explored risk factors in children and women using data from Bhutan's National Nutrition Survey 2015. Prevalence was calculated using life‐stage‐specific cut‐offs adjusted for altitude and survey design. Risk factors were evaluated in modified Poisson regressions. Anaemia affected 42%, 29%, 36%, and 28% of children, adolescent girls, and non‐pregnant and pregnant women, respectively. Risk of anaemia was greater in children who were younger (RR 2.0, 95% CI [1.7, 2.3] and RR 1.9, 95% CI [1.6, 2.3], respectively, for 12–23 and 6–11 vs. 24–59 months), male (1.2, 1.1–1.4, ref.: female), and stunted (1.2, 1.0–1.3, ref.: height‐for‐age ≥ −2z). Older (15–19 years) versus younger (10–14 years) adolescents were at higher risk (1.5, 1.2–1.8), as were adolescents living at home versus at school (1.2, 0.9–1.6) and those working versus studying (1.3, 1.0–1.7). Among adult women, anaemia risk increased with age (1.2, 1.0–1.4 and 1.3, 1.1–1.5, for 30–39 and 40–49, respectively, vs. 20–29 years) and was higher for women without schooling (1.1, 1.0–1.3, vs. primary schooling), who were unmarried or separated (1.4, 1.2–1.7 and 1.3, 1.1–1.6, respectively, vs. married), without a child <5 years (1.1, 1.0–1.3), and lacking improved sanitation (1.1, 1.0–1.3). High coverage of antennal iron and folic acid supplementation may contribute to the lower prevalence of anaemia among pregnant women and women with young children. Expansion of iron supplementation programmes, fortification, and other strategies to improve dietary iron intake may reduce the prevalence of anaemia, but causes of anaemia other than iron deficiency (e.g., thalassemias) should also be investigated.